Piezo1 channels sense whole body physical activity to reset cardiovascular homeostasis and enhance performance - Baptiste Rode (Nature Portfolio, 2017)
The mechanisms that regulate the body’s response to exercise are poorly understood. Here, Rode et al. show that the mechanically activated cation channel Piezo1 is a molecular sensor of physical exercise in the endothelium that triggers endothelial communication to mesenteric vessel muscle cells, leading to vasoconstriction.